Investigating and developing the best method in shortest path for implementing a geographical information system (e-map) for Peninsular Malaysia - Ahmad, Ab. Rahman; Zenon , Nasaruddin; Hassan, Haswadi (Faculty of Computer Science and Information System, 2005)
The shortest path is a part of the subject in the graph theory in the field of operational research. The idea of the shortest path is to find the best possible routes that linking between a given source and a destination. There are many algorithms have been designed to find these paths. The algorithms such as Djikstra, Bellman-Ford or Floyd- Warshall are difference from one to another due to the simplicity, effectiveness and duration of processing the nodes. This research will be focused on determining the best shortest path algorithm for the first possible best (fastest, safest and cheapest) route and also to search the other possible best routes. Assessment will be done by calculating the algorithm complexion and runtime using the computer. The fastest route can be attained via traveling on the highway. The safest route is might considered as a route with an accident free (data from police department). The cheapest route is a toll-free route, i.e., federal or state routes. The numbering assigned to every route in Peninsular Malaysia will be used to calculate and distinguish these routes and the alternatives. A development of GIS database is also involved in prototype covering the road network in Peninsular Malaysia (the e-map) will be developed to show the viability or validity of the findings. The system will be developed by using Microsoft Visual Basic and some supporting software. It is hoped the system will serve at test platform for the deeper research in the future.